Erdheim–Chester disease. Issue 4 (August 2020) - Starkebaum, Gordon; Hendrie, Paul
Abstract: Erdheim–Chester disease (ECD) is a rare but increasingly recognized multi-system disorder. Its diagnosis and treatment require integration of clinical information, imaging studies, and pathology studies. Of note, ECD can now be defined as a clonal myeloid disorder due to mutations which activate mitogen-activated protein kinase (MAPK) pathways and where an inflammatory milieu is important in the pathogenesis and clinical manifestations of the disease. Biopsy demonstrating characteristic histopathologic features in addition to clinical and radiographic features, most often sclerosing long bone involvement, is required to establish a diagnosis. Detection of somatic MAPK pathway mutations can also assist in the differential diagnosis of ECD and related histiocytic neoplasms. Also, genetic analysis establishing BRAF and RAS mutational status is critical in all ECD patients, as these features will impact therapy with MAPK inhibition. Therapy is recommended at diagnosis in all patients, except for those patients with minimally symptomatic disease. Prospective therapeutic trials are essential to furthering therapeutic progress in ECD.